2022
DOI: 10.4093/dmj.2021.0099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetic Retinopathy in Undiagnosed Diabetic Patients: A Nationwide Population-Based Study

Abstract: Background:We investigated the prevalence of diabetic retinopathy (DR) in patients with undiagnosed diabetes through a nationwide survey, compared to those with known diabetes. Methods: Among the participants of the Korean National Health and Nutrition Examination Surveys (KNHANES) from 2017 to 2018, individuals aged ≥40 years with diabetes and fundus exam results were enrolled. Sampling weights were applied to represent the entire Korean population. Newly detected diabetes patients through KNHANES were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, 7.3% to 18.2% of patients already have DR at the time of diabetes diagnosis, and a previous study reported that among patients with DM, DR might develop 4 to 7 years before the diagnosis of diabetes ( 25 ). Undiagnosed diabetes might have comparable DR risk among those with already known diabetes ( 26 ). Retinopathy lesions may represent early microvascular damage from a combination of insults by various risk factors and individual with different glucose metabolism status susceptibilities to such insults.…”
Section: Discussionmentioning
confidence: 99%
“…However, 7.3% to 18.2% of patients already have DR at the time of diabetes diagnosis, and a previous study reported that among patients with DM, DR might develop 4 to 7 years before the diagnosis of diabetes ( 25 ). Undiagnosed diabetes might have comparable DR risk among those with already known diabetes ( 26 ). Retinopathy lesions may represent early microvascular damage from a combination of insults by various risk factors and individual with different glucose metabolism status susceptibilities to such insults.…”
Section: Discussionmentioning
confidence: 99%
“…present, DR is mainly detected through early screening. However, due to the limitations of screening, when DR is found, characteristic blood vessel changes have already occurred in the fundus, which endangers vision [24]. Although the effects of RNV can be mitigated by laser photocoagulation or injection of anti-VEGF drugs, because the mechanism of RNV is not yet de nite, there is still no effective method for the treatment of DR [25].…”
Section: Discussionmentioning
confidence: 99%
“…Because participants in the KNHANES were sampled using a stratified, multistage probability cluster sampling design to represent the whole Korean population [ 22 , 23 ], complex sample analysis was necessary for the present data. Data for men and women were separately analyzed because of sex differences in the formulae for the visceral adiposity indices.…”
Section: Methodsmentioning
confidence: 99%